Beyond blood gases: diaphragm-guided sequential non-invasive ventilation for COPD with type II respiratory failure - Yige Wang; Lu Yao; Qiang Xiao; Yafen Tan (Frontiers in Medicine, 2026)
Chronic obstructive pulmonary disease (COPD) with type II respiratory failure is driven by diaphragm load–capacity imbalance and abnormal central respiratory drive, yet clinical decision-making for sequential non-invasive ventilation (NIV) remains largely dependent on blood gas normalization. This narrative review, informed by a structured literature search of PubMed, Embase, and Cochrane Library (January 2000 to June 2026), synthesizes physiological evidence supporting a shift from blood gas–guided to diaphragm–guided sequential NIV management. We propose a testable, three-tier conceptual framework stratified by bedside-measured diaphragmatic thickening fraction (DTF): patients with DTF below 20% may experience severe diaphragmatic impairment requiring sustained high-intensity spontaneous/timed ventilation; those with DTF between 20 and 30% likely retain limited reserve suited to adaptive average volume-assured pressure support as a transitional bridge; and patients with DTF above 30% presumably possess sufficient muscle recovery to transition to proportional assist ventilation or neurally adjusted ventilatory assist for diaphragmatic conditioning. These DTF cutoffs and corresponding mode allocations are provisional hypotheses extrapolated from acute NIV and ICU weaning cohorts and require prospective multicenter validation before routine clinical use. This work addresses three key evidence gaps: longitudinal peri-transition DTF trajectories, ventilation mode comparisons with diaphragmatic functional endpoints, and unconfirmed stratification thresholds, with dedicated prospective trial designs proposed accordingly. Importantly, conventional blood gas assessment remains the validated core standard of care, and this DTF-based strategy only serves as an adjunct physiological tool. Combined serial diaphragmatic ultrasound and respiratory drive monitoring shifts clinical focus from passive biochemical correction to comprehensive physiological recovery, delivering an individualized, physiology-centered strategy to mitigate ventilatory transition failure in advanced COPD.